Urticarial Vasculitis-Associated Intestinal Ischemia - Uni Wong; Harris Yfantis; Guofeng Xie (Case Reports in Gastrointestinal Medicine)
Urticarial vasculitis (UV) is a rare small vessel vasculitis. UV is often idiopathic but can also present in the context of autoimmune disorders such as systemic lupus erythematosus, drug reactions, infections, or a paraneoplastic syndrome. Extracutaneous complications include intestinal ischemic injuries, in UV patients with nonspecific gastrointestinal symptoms such as abdominal pain and nausea. Prompt recognition and treatment can minimize morbidity and mortality. This paper describes a case of urticarial vasculitis-associated intestinal ischemia.